XRN1 deletion induces PKR-dependent cell lethality in interferon-activated cancer cells - Tao Zou; Meng Zhou; Akansha Gupta; Patrick Zhuang; Alyssa R. Fishbein; Hope Y. Wei; Diego Capcha-Rodriguez; Zhouwei Zhang; Andrew D. Cherniack; Matthew Meyerson (Cell Reports, 2024)
Summary: Emerging data suggest that induction of viral mimicry responses through activation of double-stranded RNA (dsRNA) sensors in cancer cells is a promising therapeutic strategy. One approach to induce viral mimicry is to target molecular regulators of dsRNA sensing pathways. Here, we show that the exoribonuclease XRN1 is a negative regulator of the dsRNA sensor protein kinase R (PKR) in cancer cells with high interferon-stimulated gene expression. XRN1 deletion causes PKR pathway activation and consequent cancer cell lethality. Disruption of interferon signaling with the JAK1/2 inhibitor ruxolitinib can decrease cellular PKR levels and rescue sensitivity to XRN1 deletion. Conversely, interferon-β stimulation can increase PKR levels and induce sensitivity to XRN1 inactivation. Lastly, XRN1 deletion causes accumulation of endogenous complementary sense/anti-sense RNAs, which may represent candidate PKR ligands. Our data demonstrate how XRN1 regulates PKR and how this interaction creates a vulnerability in cancer cells with an activated interferon cell state.